Oppression and Identity in Bradbury’s Fahrenheit 451 - Amalia Dwi Utami (Universitas Pendidikan Indonesia (UPI), 2015)
This research investigates the representation of Jokowi’s figure as the governor of Jakarta, the presidential candidate, and the President of Indonesia in the Jakarta Post by using nomination and predication strategies of Discourse Historical Approach (DHA) proposed by Reisigl and Wodak (2009). By employing descriptive qualitative method, this research examines fifteen editorials focusing on Jokowi. The findings reveal three main points. First, deixis and synecdoches become the nomination strategies that signify changes. The strategies signal that the Jakarta Post prefers to focus on Jokowi when he becomes the president since his every action represents the action that the government and Indonesia take. Second, the Jakarta Post prefers to use positive predication strategies in presenting Jokowi’s figure in all categories except in the KPK issue. Third, the signification of the representation indicates that nomination and predication strategies are employed to represent the shift in political support towards Jokowi: from positive to negative. The Jakarta Post supports Jokowi since his performance as a leader is in line with the Jakarta Post values. However, the fact that the Jakarta Post no longer gives him its full support on the KPK issue indicates that his action contradicts the Jakarta Post’s ideology that supports anticorruption movement.Keywords: Jokowi, the Jakarta Post, discourse historical approach, nomination strategies, predication strategies